2022
DOI: 10.1029/2021ja030193
|View full text |Cite
|
Sign up to set email alerts
|

The Seed Populations in the Earth's Outer Radiation Belt During the Main Phase of Magnetic Storms: A Statistical Study

Abstract: Using the data from Van Allen Probes, we investigate in detail the seed populations in the outer radiation belt during the storm main phase. Based on the different flux variations of the seed electrons before the storm and around the storm peak, these storm events are divided into “flux decay events,” “flux enhancement events” and “strong flux enhancement events.” For flux decay events, a shorter storm main phase (≤12 hr) and smaller southward interplanetary magnetic field (IMF) and solar wind electric field (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…The chorus waves are well correlated with substorm intensity (e.g., Agapitov et al., 2013; Kim et al., 2015; Meredith et al., 2001, 2012; D. Wang et al., 2019). During the intense substorms, substorm electron injections or magnetospheric convection also provide the seed populations (e.g., Gabrielse et al., 2012; Khoo et al., 2019; Tang et al., 2013; X. Wang et al., 2022; Zhao et al., 2016), which can be energized to MeV energies by wave‐particle interactions (e.g., W. Li et al., 2014; Thorne et al., 2013). However, Meredith et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chorus waves are well correlated with substorm intensity (e.g., Agapitov et al., 2013; Kim et al., 2015; Meredith et al., 2001, 2012; D. Wang et al., 2019). During the intense substorms, substorm electron injections or magnetospheric convection also provide the seed populations (e.g., Gabrielse et al., 2012; Khoo et al., 2019; Tang et al., 2013; X. Wang et al., 2022; Zhao et al., 2016), which can be energized to MeV energies by wave‐particle interactions (e.g., W. Li et al., 2014; Thorne et al., 2013). However, Meredith et al.…”
Section: Discussionmentioning
confidence: 99%
“…The acceleration mechanisms of relativistic electrons are mainly local acceleration and inward radial diffusion. For the local acceleration process, the seed electrons (∼hundred kiloelectron volts) from substorm injections or magnetospheric convection (e.g., Tang et al., 2009, 2018; X. Wang et al., 2022) are locally accelerated to relativistic energies by whistler‐mode chorus waves (e.g., Boyd et al., 2014; Horne & Thorne, 1998; L. Y. Li et al., 2005; Miyoshi et al., 2013; Mourenas et al., 2014; Omura et al., 2015). Previous studies have also shown that the local acceleration process involved energetic electrons in nonlinear interactions with chorus waves (e.g., Foster et al., 2017; Mozer et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…L. Tang et al, 2017b;Turner et al, 2015Turner et al, , 2019. Wang et al (2022) have shown that the flux variations of the seed electrons during the storm main phase are highly influenced by the duration of the storm main phase, southward IMF, and solar wind electric field. Turner et al (2019) suggested the seed electron fluxes at ∼3 ≤ L ≤ ∼ 4 increased during the main phase of most magnetic storms and then decayed gradually during the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the seed populations (100s keV) in the outer radiation belt have different generation or acceleration mechanisms. Usually, the seed populations mainly come from storm convection and substorm electron injections (e.g., Baker et al., 2016; Kissinger et al., 2014; Y. Y. Shprits et al., 2015; C. L. Tang et al., 2010, 2013, 2018; Tang, Zhou, et al., 2016; Wang et al., 2022). The chorus waves (e.g., Ma et al., 2016), fast magnetosonic waves (Turner et al., 2015), and ULF waves (e.g., C. L. Tang et al., 2018) can contribute to the generation of the seed populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation